Penerimaan Negara Bukan Pajak Pada Satuan Kerja Penataan Bangunan Dan Lingkungan Provinsi Kalimantan Selatan - iskandar, dahliana (INOVATOR, 2020)
The issuance of the Minister of Finance Regulation No. 138 / PMK.06 / 2010 of 2010 and the Minister of Finance Regulation No. 246 / PMK.06 / 2014 of 2014, concerning changes to the legislation in the field of management of State Property resulted in the management of State Homes, faced with several obstacles. Determination of the status of a state house is a decision of the Minister of Public Works and Public Housing in this case the Director General of Human Settlements determining the status of a Group I, II, or III State House that is independent and / or in the form of a Flats Unit along with or not with its land. The number of State House Groups II and III are still unclear about the management of their documents because they are no longer inhabited by the original inhabitants in accordance with the Decree of the State House, and there are even houses where there are no more locations and have been sold to the community. The government must regulate the State Homes of Groups I, II, and III to increase Non-Tax State Revenues